Intervensi Keperawatan Komunitas dalam Mengantisipasi Bullyng di Sekolah - Nugraha, Yophi; Suharno, Suharno (Journal of Telenursing (JOTING), 2023)
This research aims to determine nursing interventions in the community in dealing with bullying at school. The method used is library research and a descriptive qualitative approach with data collection carried out based on source search techniques, the process of understanding and analyzing and constructing various sources such as books, journals and various research related to community nursing interventions in anticipating bullying in schools. The research results show that community-based nursing interventions to overcome bullying in the school environment include bullying prevention programs in schools, group counseling and health education. In conclusion, in general, school-based bullying prevention interventions by increasing students' knowledge of bullying and victimization can therefore reduce the number of cases of bullying among students, and obtain much better results. Keywords: Bullying, Community Nursing Intervention, School